Конские налобники из новолабинского погребения 71 и курганов у с. Глиное как индикатор контактов Поднестровья и Прикубанья - Раев, Б.А. (Археологія і давня історія України, 2020)
В статье публикуются материалы конского захоронения Новолабинского могильника (Прикубанье) с несколькими комплектами снаряжения верхового коня — удилами с псалиями, бляхами оголовья и налобниками. По аналогиям из курганов Азиатского Боспора комплекс датируется серединой II в. до н. э. Налобники с крючком, аналогичные новолабинским, были найдены в курганах у с. Глиное на Днестре в погребениях второй четверти II в. до н. э. Специфический элемент конской узды — налобник с крючком и секировидной лопастью — диагностирует переселение части скифского населения, оставившего Тираспольские курганы, в Северо-Западное Предкавказье, о котором писал А. В. Симоненко. This publication presents an assemblage from a horse burial excavated in 2011 in the cemetery of the 4th Novolabinsky settlement in the Kuban region. Six horses placed in a pit, were accompanied by several sets of riding harness. It included one bit with straight check-pieces, C-shaped check-pieces, bridle decorations, breastgirth ornaments and three frontlets, each with a hook, two of them have zoomorphic ends. The closest parallels to the horse frontlets from the Bolshoi Kurgan of Vasyurinskaya Gora allow us to attribute the Novolabinsk grave to the 2nd century BC. A series of eight similar frontlets without zoomorphic décor was found in kurgans near the village of Glinoe in Transnistria. The excavators dated the assemblages to the period from the first half of the 3rd century ВС to the first half of the 2nd century BC. Meanwhile, during this period there was a significant gap in 20—30 years when frontlets were not found in the graves. Considering the typological closeness of the Transnistrian and Kuban frontlets, the chronological gap looked questionable. Re-evaluation of the data of the Tiraspol kurgans, and an analysis of the grounds for their dating revealed that the authors of their initial publication assigned the materials to 15—90 years older. Assemblages with frontlets from kurgans near the village of Glinoe, according to the revised dating, make up a compact group, and a time period between the earliest and latest burials was no more than 50— 60 years, from the first decade to the third quarter of the 2nd century BC. The revision and specification of the dates of the Tiraspol kurgans reduces to a minimum the time gap between the graves with frontlets in the Transnistria and the graves with frontlets in the Kuban region. Such a chronology confirms the possibility of a hypothesis formulated in 2016 by A. V. Symonenko, according to which a part of the Tiraspol elite returned to the native lands of the North-Western Ciscaucasia. It was in the Kuban region, when zoomorphic decorative elements, as a result of an influence of the antique centers of the Black Sea region, appeared on frontlets with hook. The high quality of the frontlets from Kuban region, expressed not only in the décor but in the complicated technique of combining several metals (iron, silver, bronze, and gold) in the same object, was due to their manufacturing in the Bosporus workshops. Статтю присвячено публікації матеріалів кінського поховання, розкопаного у 2011 р. в могильнику 4 Новолабінського городища в Прикубанні. Шість коней, покладених в яму, супроводжувалися кількома комплектами спорядження верхового коня. До нього входили вудила із жорсткими насадками, С-подібні псалії, бляхи оголов’я, нагрудники та три налобники з гачком, два з яких завершуються зооморфними зображеннями. Найближчі аналогії кінським налобникам з Великого кургану Васюринської гори дозволяють віднести новолабінське поховання до II ст. до н. е. Серію з восьми подібних налобників, але без зооморфних елементів, було знайдено в курганах у с. Глиноє в Придністров’ї. Авторське датування комплексів відносило їх до періоду від першої половини III ст. до н. е. до першої половини II ст. до н. е., із значним для одного могильника проміжком в 20— 30 років, коли таких налобників в курганах взагалі немає. При типологічній близькості придністровських і прикубанських налобників дивним виглядав хронологічний розрив між похованнями, в яких вони знайдені. Звернення до матеріалів Тираспольських курганів і перевірка підстав для їх датування виявили тенденцію авторів публікації могильника до заниження дат курганів на 15—90 років. Комплекси з налобниками з курганів у с. Глиноє за уточненими датуваннями становлять компактну групу, час здійснення поховань в якій становить не більше 50—60 років. Перегляд та уточнення дат Тираспольських курганів до мінімуму скорочує розрив між ними і прикубанськими похованнями з налобниками. Така хронологія підтверджує можливість гіпотези, сформульованої у 2016 р. О. В . Симоненком, про повернення частини тираспольської еліти на споконвічні землі Північно-Західного Передкавказзя. Вже у Прикубанні на налобниках з гачком з’являються зооморфні елементи декору, пов’язані з впливом античних центрів Причорномор’я. Висока якість налобників з Прикубання, що відбилася не тільки в декорі, але й у складній техніці з’єднання в одному виробі кількох металів (заліза, срібла, бронзи, золота), було зумовлено виготовленням їх у майстернях Боспора.